Comorbidity in Atopic Dermatitis - Simpson, Eric L. (2012)
The negative impact of atopic dermatitis (AD) often extends beyond the skin. Children with AD experience increased rates of infectious, mental health, and allergic diseases compared to their non-atopic peers. The mechanisms underlying these associations remain elusive. New insights from genetic and epidermal research pinpoint the skin barrier as a primary initiator of AD. Epicutaneous sensitization represents an intriguing new model which links a disrupted skin barrier to the later development of IgE-mediated diseases in patients with AD. Recent epidemiological studies have identified new comorbidities linked to AD as well, including several mental health disorders and obesity. This manuscript reviews the recent literature regarding both classic and newly described AD comorbidities.